Anaerobic bacteraemia: A score predicting mortality. (August 2020) - Cobo, Fernando; Aliaga, Luis; Expósito-Ruiz, Manuela; Navarro-Marí, José María
Abstract: The objectives of this study were to report those variables which are readily identifiable at the bedside and that are able to predict mortality in patients with bacteraemia caused by anaerobes. Patients with clinically significant anaerobic bacteraemias detected between January 2016 and December 2019 in a tertiary hospital in Granada (Spain) were retrospectively included. Species identification was performed by MALDI-TOF MS and/or molecular methods. Finally, 136 cases of anaerobic bacteraemia were included, being the most frequent anaerobes Bacteroides (45.5%; n = 62), Clostridium (24.2%, n = 33), and Gram-positive anaerobic cocci (16.1%, n = 22). Crude mortality was 25.7%, corresponding to 35 patients who died, with 82.8% of deaths directly attributable to bacteraemia. A multivariable logistic regression model with non-parametric bootstrap estimation identified three variables that were independently and significantly associated with an increased risk of death: 1) hospitalization in the intensive care unit; 2) septic shock; and 3) presence of any kind of cancer. These variables were as recorded at the time that the first positive blood culture was obtained. An index score, obtained from these variables, was calculated and divided patients into two groups with increasing likelihood of mortality resulting from anaerobic bacteraemia. The sensitivity and specificity of a prediction of death based on this model were 65.2% and 97%, respectively. Highlights: Anaerobic bacteraemia accounted for 1.32 cases per 1000 admissions. In 77.2% of all anaerobic bacteraemias were involved Bacteroides, Clostridium and Fusobacterium. Crude mortality for anaerobic bacteraemia was 25.7%. Septic shock, admission in ICU and presence of cancer were associated with high risk or mortality.